(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
It is shown that metal nanoparticles with thin atomic surface layer can be used as laser active medium. Significant narrowing of the emission band in the spectrum of the particle with a surface layer was found.